Effectiveness of Transformative Learning Theory in Physics Laboratories of Physics Students of Mongolian National University of Education(MNUE) - Ochirbat, Altangoo; Badarch, Gantuya; Khankhuu , Batbold (Lavai - International Journal of Education, 2024)
As part of the conceptual reform of the curriculum, the orientation of changes in content, teaching methods, and evaluation are defined by the principles of “Simplifying Content, Amplifying Methodology, and Amplifying Process Evaluation”. In this study, we examined how Transformative Learning Theory can be applied to enhance students' scientific inquiry abilities in the "Practicum of Physics Experiment" course within the MNUE’s Physics Teacher Training Program. The discussion focuses on developing a teaching and learning method for the physics laboratory, rooted in Transformative Learning Theory, to improve the experimental proficiency of Physics students at MNUE. The findings of the experimental study demonstrate a notable enhancement in students' initial average score across various domains. Specifically, there was an increase of 2.57 points in conceptual knowledge, 2.61 points in planning skills, 2.75 points in the skills related to conducting experiments and collecting data, and 2.31 points in data analysis skills. When the students' laboratory performance evaluation results were analyzed using a t-test, the results showed t = -43.096 and p = 0.001, indicating a statistically significant differences between pre and post-test.